2007
DOI: 10.1177/1078390307305171
|View full text |Cite
|
Sign up to set email alerts
|

APNA and ANCC Collaboration: Achieving Consensus on Future Credentialing for Advanced Practice Psychiatric and Mental Health Nursing

Abstract: The American Psychiatric Nurses Association and the American Nurses Credentialing Center conducted a logical job analysis based on three recent role-delineation studies (RDSs) to determine whether there was enough commonality in the practice of psychiatric and mental health nursing by clinical nurse specialists (PMH-CS) and nurse practitioners (PMH-NP) to support the development of a single certification examination. Three hundred seventy-one work tasks gleaned from the three RDSs were presented for systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
(3 reference statements)
0
9
0
Order By: Relevance
“…This recommendation is particularly relevant to nursing practice. Nurses are trained to deliver holistic care that considers the interpersonal, psychological, and social circumstances that affect the mental and emotional well‐being of patients and their families (Rice, Moller, DePascale, & Skinner, ). Below we discuss relationships between Jordanian adolescents’ characteristics and depression severity, and ways to tackle depression both clinically and in research.…”
Section: Discussionmentioning
confidence: 99%
“…This recommendation is particularly relevant to nursing practice. Nurses are trained to deliver holistic care that considers the interpersonal, psychological, and social circumstances that affect the mental and emotional well‐being of patients and their families (Rice, Moller, DePascale, & Skinner, ). Below we discuss relationships between Jordanian adolescents’ characteristics and depression severity, and ways to tackle depression both clinically and in research.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that at the entry level both groups of APRNs performed very similar tasks, not exactly the same, but enough overlap that they might be tested with the same adult certification exam (Rice et al, 2007). The combined APRN certification exam is soon to be offered.…”
Section: History Of the Surveymentioning
confidence: 93%
“…Both roles include the skills and knowledge to provide therapeutic interventions including psychotherapies. Further, the roles of PMHCNS and PMHNP were found by Rice, Mollar, DePasquale, and Skinner and the American Nurse Association () to have 97% congruence. The PMHNP role and the behavioral health market underwent revolutionary changes, as captured by Delaney () in The Psychiatric Nurse Practitioner 1993–2003: A Decade that Unsettled a Specialty .…”
Section: Effects Of Role Metamorphosismentioning
confidence: 99%